Diammonium‐Mediated Perovskite Film Formation for High‐Luminescence Red Perovskite Light‐Emitting Diodes. Issue 30 (22nd June 2022) - Li, Nan; Apergi, Sofia; Chan, Christopher C. S.; Jia, Yongheng; Xie, Fangyan; Liang, Qiong; Li, Gang; Wong, Kam Sing; Brocks, Geert; Tao, Shuxia; Zhao, Ni
Abstract: 3D mixed‐halide perovskite‐based red emitters combine excellent charge‐transport characteristics with simple solution processing and good film formation; however, light‐emitting diodes (LEDs) based on these emitters cannot yet outperform their nanocrystal counterparts. Here the use of diammonium halides in regulating the formation of mixed bromide–iodide perovskite films is explored. It is found that the diammonium cations preferentially bond to Pb–Br, rather than Pb–I, octahedra, promoting the formation of quasi‐2D phases. It is proposed that the perovskite formation is initially dominated by the crystallization of the thermodynamically more favorable 3D phase, but, as the solution gets depleted from the regular A cations, thin shells of amorphous quasi‐2D perovskites form. This leads to crystalline perovskite grains with efficiently passivated surfaces and reduced lattice strain. As a result, the diammonium‐treated perovskite LEDs demonstrate a record luminance (10745 cd m −2 ) and half‐lifetime among 3D perovskite‐based red LEDs. Abstract : High‐luminance red perovskite light‐emitting diodes (PeLEDs) are enabled by diammonium‐mediated perovskite formation. The diammonium halide promotes the formation of stable bromide‐rich quasi‐2D phases at the surface of 3D perovskites, leading to efficient defect passivation, suppression of ion migration, and reduced lattice strain. The optimized PeLEDs exhibit a record luminance (>10 5 cd m −2 ) and half‐lifetime (>15 h) among red‐emissive 3D PeLEDs.